Combustão iniciada por microondas e determinação em linha de cádmio e chumbo em plantas por espectrometria de absorção atômica com tubo aquecido na chama - Bartz, Fabiane Regina (2007)
In this work a new procedure is proposed by solid sampling flame furnace atomic absorption spectrometry after microwave induced combustion (MIC-FFAAS). The procedure was applied for the determination of cadmium and lead in botanical samples. Samples were groung, pressed and placed on a filter paper positioned on a quartz holder. The holder was placed in a glass device inside a microwave oven. The microwave oven was modified to make possible an oxygen inlet and the transport of the combustion products up to spectrometer. Amonium nitrate solution 50% (w/v) was used for the ignition step and O2 was used for combustion and transport of combustion products. Atomization was performed in a metalic heated tube positioned into air + acetylene flame. Deuterium background corrector was used throughout and calibration was carried out using reference solutions. After operational conditions optimization, the chosen parameters were: combustion using 20 mg of paper filter, 20 μL of NH4NO3 50% (w/v), 1 L min-1 O2 flow rate and use of tubes without modifications (for Cd) and with 12 holes (for Pb). Air and acetylene flow rates were 14 and 2 L min-1 (for Cd) and 12 and 2 L min-1 (for Pb), respectively. The system allowed the introduction up to 60 mg of sample and a quantification limit of 9.0 ng g-1 and 0.8 μg g-1, for Cd and Pb, respectively. The characteristic mass obtained was 55 pg for Cd and 4.1 ng for Pb. No significant differences were observed comparing the results using the proposed procedure with certified reference materials values or with those obtained by graphite furnace atomic absorption spectrometry and inductively coupled plasma mass spectrometry, after acid digestion. The device used for combustion and atomization may be easily coupled to flame atomic absorption spectrometters and the throughput was 20 determinations per hour, including the weighing step.